Genome-wide identification and integrated analysis of TCP genes controlling ginsenoside biosynthesis in Panax ginseng - Chang Liu; Tingting Lv; Yanhua Shen; Tao Liu; Mingming Liu; Jian Hu; Sizhang Liu; Yang Jiang; Meiping Zhang; Mingzhu Zhao; Kangyu Wang; Yi Wang (BMC Plant Biology, 2024)
Abstract Panax ginseng is an important medicinal plant, and ginsenosides are the main bioactive molecules of ginseng. The TCP (TBI, CYC, PCF) family is a group of transcription factors (TFs) that play an important role in plant growth and development, hormone signalling and synthesis of secondary metabolites. In our study, 78 PgTCP transcripts were identified from the established ginseng transcriptome database. A phylogenetic tree analysis showed that the 67 PgTCP transcripts with complete open reading frames were classified into three subfamilies, including CIN, PCF, and CYC/TB1. Protein structure analysis showed that PgTCP genes had bHLH structures. Chromosomal localization analysis showed that 63 PgTCP genes were localized on 17 of the 24 chromosomes of the Chinese ginseng genome. Expression pattern analysis showed that PgTCP genes differed among different lineages and were spatiotemporally specific. Coexpression network analysis indicated that PgTCP genes were coexpressed and involved in plant activities or metabolic regulation in ginseng. The expression levels of PgTCP genes from class I (PCF) were significantly downregulated, while the expression levels of PgTCP genes from class II (CIN and CYC/TB1) were upregulated, suggesting that TCP genes may be involved in the regulation of secondary metabolism in ginseng. As the PgTCP26-02 gene was found to be related to ginsenoside synthesis, its predicted protein structure and expression pattern were further analysed. Our results provide new insights into the origin, differentiation, evolution and function of the PgTCP gene family in ginseng, as well as the regulation of plant secondary metabolism.